Medical education during the coronavirus disease 2019 pandemic: an umbrella review - Nejadghaderi, Seyed Aria; Khoshgoftar, Zohreh; Fazlollahi, Asra; Nasiri, Mohammad Javad (Frontiers in Medicine, 2024)
Background: The coronavirus disease 2019 (COVID-19) pandemic affected many aspects of lifestyle and medical education during the recent years. We aimed to determine the impacts of COVID-19 pandemic on medical education to provide an overview of systematic reviews on it. Methods: We searched PubMed, Scopus, Web of Science, Cochrane library, Google Scholar, and medRxiv, with the following keywords: “SARS-CoV-2”, “COVID-19”, “Medical Education”, “E-learning”, “Distance Education”, “Online Learning”, “Virtual Education”, “systematic review”, and “meta-analysis”, up to 15 April 2023. Studies were included if they were systematic reviews assessing the impacts of the COVID-19 pandemic on medical sciences students. We used A MeaSurement Tool to Assess systematic Reviews 2 (AMSTAR-2) checklist for quality assessment. Results: A total of 28 systematic reviews were included. The eligible reviews included between five and 64 primary studies, ranging from 897 to 139381 participants. Technology-enhanced learning and simulation-based learning were the most frequently used strategies. Virtual teaching has several drawbacks like technical difficulties, confidentiality problems, lower student involvement, connection problems, and digital fatigue. The overall satisfaction rate for online learning was above 50%. Also, favorable opinions about perception, acceptability, motivation, and engagement were reported. The quality of 27 studies were critically low and one was low. Conclusions: There were reduced clinical exposure and satisfaction for medical students during the pandemic. Further high-quality systematic reviews are required.